2023
DOI: 10.3390/atmos14061004
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Prenatal Mosquito Coil Smoke Exposure and Early Postnatal Nutritional Status on Obesity among Preschoolers

Abstract: Informed by the theory of developmental origins of health and disease, we conducted a survey among 66,854 mother–preschooler dyads in all kindergartens within the Longhua District of Shenzhen in China for exploring the combined effect of prenatal mosquito coil smoke (MCS) exposure and early postnatal nutritional status on obesity in preschoolers. A self-administered questionnaire was completed by mothers to collect parents’ and children’s socio-demographic characteristics, prenatal MCS exposure, child nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…In line with these previous findings, our study found that maternal prenatal exposure to indoor air pollution of IBS was significantly linked with the presence of obesity in preschoolers, with a dose-response relationship between the frequency of trimester-specific IBS exposure in the 1st trimester and children obesity. Similarly, another recent study of ours found that prenatal exposure to indoor air pollution of mosquito coil smoke (MCS) was significantly positively associated with preschoolers' obesity [28]. In this current study, the cross-over analysis highlighted the positive association of prenatal IBS exposure in the first and second trimesters concurrently and in the whole pregnancy with obesity in preschoolers, and it indicated a dose-response relationship between maternal exposure to IBS during pregnancy and offspring obesity.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In line with these previous findings, our study found that maternal prenatal exposure to indoor air pollution of IBS was significantly linked with the presence of obesity in preschoolers, with a dose-response relationship between the frequency of trimester-specific IBS exposure in the 1st trimester and children obesity. Similarly, another recent study of ours found that prenatal exposure to indoor air pollution of mosquito coil smoke (MCS) was significantly positively associated with preschoolers' obesity [28]. In this current study, the cross-over analysis highlighted the positive association of prenatal IBS exposure in the first and second trimesters concurrently and in the whole pregnancy with obesity in preschoolers, and it indicated a dose-response relationship between maternal exposure to IBS during pregnancy and offspring obesity.…”
Section: Discussionsupporting
confidence: 75%
“…For example, Rueda-Clausen et al found that prenatal hypoxia and postnatal high-fat diets in offspring were associated with an increased myocardial susceptibility to ischemia [27]. In addition, our recent study found that prenatal mosquito coil smoke exposure and early postnatal nutrition status can independently and jointly increase the risk of preschoolers' obesity [28].…”
Section: Introductionmentioning
confidence: 61%